'Biohoarding': treasures not seen, stories not told. (April 2016) - Catchpoole, Daniel
This article raises the concern that biobanks are failing to realize the expected research and health service outcomes. Rather than biobanking, we have been engaging in 'biohoarding', where building a quantifiable collection of tissue samples is the primary basis of the bio-resource. The root cause of 'biohoarding' is an ideological and motivational confusion as to the purpose for collecting the tissue in the first place. We have lost sight of the knowledge gain that biobanks should generate. The obligation to prevent 'biohoarding' lies not with researchers, funders or managers but with policy makers.